Detection of Carbamazepine Level among Patients Visiting Psychiatric and Pediatric Services of a Tertiary Hospital in Eastern Nepal - Panday, Dipesh Raj; Rauniar, Gajendra Prasad; Rai, Dilli Sher; Panday, Karishma Rajbhandari; Basnet, Madhur; Kafle, Shyam Prasad (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: Carbamazepine plasma level is directly related to dose, therapeutic effect, and toxicity. We aimed to observe its plasma level and relationship with dose among psychiatric and pediatric patients. Methods: This observational study was performed in the Therapeutic Drug Monitoring Laboratory of a university hospital for a period of 1.5 years. Twenty-six consenting patients visiting either psychiatric or pediatric service and taking carbamazepine same dose for > 8 days (i.e. > 6 half-lives) were enrolled. The primary outcome was plasma carbamazepine level as determined by a High-Performance Liquid Chromatography machine. The secondary outcome included its correlation with dose assessed by the Spearman rho’s correlation coefficient. Results: The mean dose received by the patients was 13.31 ± 5.39 mg/kg/day in pediatrics and 8.33 ± 2.29 mg/kg/day in psychiatry. The plasma levels [median (IQR)] were 10.01 (6.27, 13.35) mg/L and 10.53 (5.17, 15.19) mg/L respectively in pediatric and psychiatric patients. Thirteen patients (50%) had therapeutic, 10 (36.46%) had above therapeutic, and 3 (11.54%) had subtherapeutic plasma level. Neurocysticercosis (23.1%) in pediatrics and partial seizure (69%) in psychiatry were the most common diagnosis. Symptom-control was achieved in 19 (73.1%) patients. The plasma carbamazepine level did not correlate with dose either in pediatric patients (p = 0.42) or in psychiatry patients (p = 0.63). Conclusion: The plasma carbamazepine levels [median (IQR)] in pediatric and psychiatric patients were 10.01 (6.27, 13.35) mg/L and 10.53 (5.17, 15.19) mg/L respectively. The plasma level was normal in half of the recruited patients and did not correlate with dose.